Investigation of some changes and clonal relationship in enterococci isolates due to relocation of a hospital - Korkoca, Hanifi; Hazirolan, Gulsen; Cicek, Cemal; Savas, Sumeyra; Akgul, Omer; Tanriverdi, Elif Seren (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the isolation rates, antimicrobial resistance rates, minimum inhibitory concentration values of antimicrobial agents, and clonal relationships of Enterococcus faecalis and Enterococcus faecium due to the relocation of a hospital to a newly constructed building. Method: The comparative, prospective study was conducted at adult general intensive care units of the Mus State Hospital, Mus, Turkey, in two phases; before the relocation from January 25 to December 1, 2014, and after the relocation from February 10 to May 24, 2015. Rectal swab samples were collected 72 hours post-hospitalisation. Identification of Enterococcus faecalis and Enterococcus faecium isolates was determined by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, and antimicrobial resistance with minimum inhibitory concentration values was detected with Vitek 2 system. The clonal relatedness among the strains was investigated by pulsed-field gel electrophoresis. Data was analysed using SPSS 23. Results: Of the 69 patients, 37(53.62%) related to pre-relocation phase; 20(54.1%) females and 17(45.9%) males with mean age 62.81±21.71 years. There were 32(46.37%) patients in the post-relocation phase; 13(40.6%) females and 19(59.4%) males with mean age 62.69±21.35 years (p>0.05). Of the 84 enterococci strains isolated, 51(60.7%) were Enterococcus faecium; 28(55%) before relocation and 23(45%) after relocation (p=0.77). The remaining 33(39.3%) isolates were Enterococcus faecalis; 16(48.5%) before relocation and 17(51.5%) after relocation (p=0.73). Multiple strains were located in 7(18.9%) patients before relocation and in 7(21.9%) after relocation. In 1(3.1%) patient after relocation, 2(8.7%) Enterococcus faecium isolates with different resistance and pulsed-field gel electrophoresis patterns were detected. There were no significant differences between the isolation and antibiotic resistance rates before and after relocation (p>0.05), and a clonal relation between the isolates was not detected (p>0.05). Decreased minimum inhibitory concentration values were noted for some antibiotics (p<0.05). Conclusion: Clonal relationship between the isolates and change in the rates of isolation and antimicrobial resistance of Enterococcus faecalis and Enterococcus faecium was detected due to relocation. Minimum inhibitory concentration values could be used to reveal relocation-related changes in isolates obtained from patients hospitalised in intensive care units. Key Words: Enterococcus, Antimicrobial drug resistance, Transmission, Hospital moving.